Why exporting countries agree voluntary export restraints: The oligopolistic power of the foreign supplier - Roberto A. De Santis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This study analytically shows that a VER serves as an institution to protect incumbent firms of an exporting country. A VER is an entry barrier in the export market. It favours the concentration of industry, and allows established firms to better exploit economies of scale by producing output at lower average cost. Since the break-even price for potential firms is the average cost, entry in the domestic market is also inhibited, regardless of the form of competition. A VER also allows the raising of the price cost margin in the export market. However, the smaller the country, the greater the possibility also of a larger monopoly power in the domestic market. The impact on firm size is ambiguous. From the social point of view, three conventional effects from the elimination of a VER are usually considered: the rent loss effect, the efficiency effect and the export producer price effect. In this study, two further effects on welfare are examined: the increased intermediate inputs cost effect and the variety effect. The global effect on welfare on an exporting country is analytically indeterminate. A general equilibrium model applied to Turkey supports the conjecture that with the elimination of a VER, under Bertrand or Cournot conjectures, the loss in social welfare, the higher average cost, the fall of the concentration of the industry, and the fall of monopoly power of incumbent firms, are the key elements in understanding the rationale beyond VERs.
Keywords: D58; F12; 330; VERs; Strategic Trade; AGE Analysis; Exportbeschränkung; Oligopol; Markteintritt; Außenhandelswirtschaft; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie